STUDI MANAJEMEN PEMBINAAN OLAHRAGA SEPAK BOLA DI KLUB PERSATUAN SEPAK BOLA KOTA BOGOR OLEH KANTOR PEMUDA DAN OLAHRAGA KOTA BOGOR - Wanda Maulana Haryadi; Ginung Pratidina; M.YGG Seran (LPPM Universitas Djuanda Bogor, 2016)
Factors affecting the achievement at the club include a lack of sports facilities, trainers, motivation, how to train, budget, moral support. It is no less important to note is the election strategy for football coaching at the club so that the Football Association of Bogor able to perform again.Barriers - barriers to the implementation of the Management Development of Football in the Club Football Association Bogor Based on information from the Head Chairman, Coach, and The Visitor Sport of the tabulation of data questionnaire found a number of factors which may be cited as barriers to the implementation of coaching in order to Management Coaching Football in Clubs Football Association of Bogor others as follows: (1) a lack or weakness of Infrastructures, funding and coaches in clubs PSB (2) for the factors inhibiting the Management coaching is that implementing Management coaching is still recognized the respondent adds to costs Athletes football this an interpretation of the scoring interpretation lowest figure with a score of 2:21 yangberarti Not Good. (1) Factors inhibiting Management coaching is a lack of facilities and infrastructure and completeness Sports fulfilled. (2) Inhibiting athletic performance is that the implementation of the guidance by Club Football Association Bogor weak in attention and meningatkan that athletes always achievement in football matches (3 ) efforts to solve the bottleneck problem and factor in coaching athletes football is by tersediannya facilities, infrastructure and completeness Sports fulfilled (4) efforts to address the problem of weak settlement of coaching athletes within the time set by Klub football Association of Bogor in reaching the champions necessary adannya additional fees for athletes who are able to earn achievements (champions) Keywords: Management, Development, Youth and Sports Office.